Classical modern philosophers : Descartes to Kant - Schacht, Richard, 1941- (Routledge, 1995)
Descartes, Leibniz, Spinoza, Locke, Berkeley, Hume, and Kant: these are the seven philosophers who stand out from the rest in what is known as the `modern' period in philosophy. Their thought defines the mainstream of classical or early modern philosophy, largely responsible for shaping philosophy as we now know it. In a clear and lively style, Richard Schacht has written a thorough introduction to the work of these seven founding fathers of modern philosophy. The bibliography has been updated for this revised edition to take account of the recent explosion of writings on modern philosophy.